(untitled) (Journal of history, 2025)
Since the 70s of the XIX century a new stage in the policy of the Russian Empire towards the Kazakh population began, aimed at opening professional educational institutions through which it was possible to influence in the necessary direction the formation of thinking and worldview of the younger generation. The purpose of this article is analysis of the activities of the Orenburg Kazakh Teachers’ School (1883-1917) as an institutional experiment of the empire, which for thirty-four years trained teachers for volost and aul schools. The article is based on archival documents extracted from the funds of the central archives of Kazakhstan and Russia, including office documentation (petitions, official correspondence), interaction of Kazakh seminarians with the school administration and biographical data of graduates. The methodology of the article was the postcolonial approach, including the theory of interstitial subjectivity (border / intermediate subjectivity) of Homi Bhabha. This approach will allow us to see how a graduate of the imperial teacher training school, having taken a teaching or administrative position, became an intermediary between the authorities and local society, transmitting new knowledge, new models of behavior. Moreover, the imperial educational policy for the training of Kazakh teachers had a long-term effect, as it prepared personnel for the post-imperial state, who realized their professional knowledge in the first decades of Soviet power in Kazakhstan.